Implementation of Oral Questioning in Assessing Student Learning In Mathematics Teaching In Primary Schools - et al., Muhammad Sofwan Mahmud (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
POral questioning has various roles in teaching mathematics and is often used as one of the strategies for assessing student learning formatively. However, not much is known about how primary school mathematics teachers use oral questioning to assess student learning because previous studies have focused more on oral questioning in general in terms of its implementation in teaching. Therefore, this study was conducted to explore how primary school mathematics teachers use oral questioning to assess student learning in mathematics teaching. This study is qualitative in the form of a case study involving six school mathematics teachers selected using the purposive sampling method. Data for this study were collected using observation methods, interviews and field notes. Next, the data obtained were analysed using constant comparative analysis using Atlas ti. 8 software to obtain themes and sub-themes. The study found that oral questioning helps teachers gather information about student learning to improve, make decisions on teaching and ensures that students master the topics taught. Thus, it is clear that oral questioning has a broad role in teaching, especially in assessing student learning while improving teaching quality. This study has a significant impact on teachers' instruction. The use of oral questioning needs to be intensified and expanded to enable mathematics teaching activities to be implemented more meaningfully through a formative assessment conducted through oral questioning activities.